SOSIALISASI PENGEMBANGAN STRATEGI PEMASARAN DAN PENGELOLAAN UMKM POTENSI DESA PETANANG MELALUI PENINGKATAN KEMAMPUAN SUMBER DAYA MANUSIA PROGRAM KKN TEMATIK MBKM MAHASISWA UNIVERSITAS INDO GLOBAL MANDIRI - Alfianti, Sarahdillah; Hertati, Lesi; Syafitri, Lili; Munandar, Aris; Hendarmin, Rum (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
The natural resources produced by Petanang Village are very abundant, but the natural resources owned by Petanang Village have not been fully utilized by the community, so there is a need for guidance or assistance to the community to take advantage of the existing potential. One of them is by utilizing processed cassava / sweet potato products that are made into a food with a high selling price. Seeing the problems and potentials that exist, the village community is considered to need to know more about how to process and benefit from cassava / sweet potato so that it can increase profits or can be used as a source of additional income for the community. Digital marketing is the marketing of products or services using technology via the internet, social media, cell phones, or other digital media. It is also an umbrella term that can cover a variety of digital marketing strategies such as social media marketing, search engine optimization (SEO), as well as email marketing. This digital marketing strategy is different from traditional marketing such as print media, billboards, and TV. This digital marketing strategy is certainly data driven. The purpose of digital marketing is to attract consumers and potential customers quickly. As you know, the acceptance of technology and the internet in society is very broad, so it is not surprising that digital marketing activities are the main choice for every company. As a result, every company competes with each other and competes in creating interesting content to be displayed in its marketing in cyberspace.